The EU-Thailand relations tracing the patterns of new bilateralism - Kiatpongsan, Chaiyakorn (IIAS publications series, 2011)
This book focuses on the so-called 'new bilateralism' phenomenon, a foreign policy development that has widespread across regions since the mid-1990s. The book asks why the policy trend of 'new bilateralism' has been pursued in spite of the widely accepted views on political and economic advantages of 'multilateralism'.